A Similarity, does it necessary mean plagiarism? Stop intentional and exaggerated paraphrasing - Shohda, Eslam Elsayed Ali (Nepal Journal of Epidemiology, 2021)
During the last two decades, programs have been relied on to detect scientific plagiarism, as it is found that some authors use previous published results or scientific ideas without attributing them to their original authors. But the term similarity has been confused with scientific plagiarism. This led to the need for procedures that are not justified by intuition of mind, and led to the difficulty of conducting important research, unnecessary time wasting and difficulties.